Culture and Stock Market Impact From Bad News Announcements - Liu, Jiangxia (Journal of Applied Business and Economics, 2021)
Bad news causes a decline in the stockholder’s wealth. However, the magnitude of the impact varies between studies. Intending to explain the different impacts observed, we explore the factors affecting the extent of stock impact from bad news announcement. Event Study Methodology is used to analyze data from the US, India, and Japan. The rich multinational data allows the comparison of stock impact between countries. We find that disruptions cause stock decline; however, the magnitude of reduction varies between countries. We argue that national culture plays a vital role in planning and management strategies, affecting mitigation and continuity strategies. Modern companies are multinational and operate in multiple countries. Despite this, national culture is ingrained in their management styles. To explore this, we also study companies traded on stock markets outside their domicile country. We find that national culture has a strong influence on planning and preparedness. Cultural orientation impacts resiliency. We argue that investors realize the importance of culture as company domicile affects the stock impact from bad news.